2012
DOI: 10.4161/cc.11.3.18996
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A is differentially expressed in gliomas, is associated with patient survival in glioblastoma and is a potential chemotherapeutic target in gliomas

Abstract: Aurora A is critical for mitosis and is overexpressed in several neoplasms. Its overexpression transforms cultured cells, and both its overexpression and knockdown cause genomic instability. In transgenic mice, Aurora A haploinsufficiency, not overexpression, leads to increased malignant tumor formation. Aurora A thus appears to have both tumor-promoting and tumor-suppressor functions. Here, we report that Aurora A protein, measured by quantitative protein gel blotting, is differentially expressed in major gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 72 publications
4
74
0
Order By: Relevance
“…In line with the microarray gene expression profiling analysis, positive staining for AURKA is associated with an unfavorable overall survival in medulloblastoma, which is a highly malignant primary brain tumor that originates in the cerebellum or posterior fossa [12]. In addition, AURKA is differentially expressed in gliomas and is associated with patient survival in glioblastoma [13]. These results suggest that Aurora kinases may play important roles in brain tumor process and development, and can be potential targets in GBM therapy.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In line with the microarray gene expression profiling analysis, positive staining for AURKA is associated with an unfavorable overall survival in medulloblastoma, which is a highly malignant primary brain tumor that originates in the cerebellum or posterior fossa [12]. In addition, AURKA is differentially expressed in gliomas and is associated with patient survival in glioblastoma [13]. These results suggest that Aurora kinases may play important roles in brain tumor process and development, and can be potential targets in GBM therapy.…”
Section: Introductionmentioning
confidence: 89%
“…Many studies have suggested that Aurora kinases may play important roles in brain tumor development and progression [12,13,16,17,18], and inhibition of Aurora-B/C can reduce malignant glioma growth in vivo [13]. This study investigated the effects of the Aurora kinase inhibitor VE-465 on GBM cell lines and explored the underlying mechanism of the antitumor effects of VE-465 on GBM cells.…”
Section: Introductionmentioning
confidence: 99%
“…Aurora-A overexpression may be achieved not only by gene amplification but also by other mechanisms such as transcription activation or suppression of protein degradation. Several studies, carried out on different tumors, showed that AU-RKA transcription may be induced by HIF-1a, E2F3, E4TF1, TRAP220/MED1, and c-Myc [14][15][16]. However, the mechanism of transcriptional regulation of AURKA remains largely unknown, especially in BC.…”
Section: Introductionmentioning
confidence: 99%
“…The small-molecule pan-AURK inhibitor VX680 is known to suppress tumor growth in animal models (32, 43). In GBM patients, expression of AURKA in tumors is associated with poor survival (44). In vitro , AURKA inhibition in GBM cell lines was cytotoxic and potentiated by ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%